(untitled) (Journal of Science and Technology, 2016)
Population management in the developing world has become very prominent in the discussions relating to the rate and quality of development in these countries. The key question to be answered is how large is the population and at what rate it is growing. The next important question is usually, what the effect of this population and its growth rate is having on the environment. The paper tries to seek some answers to these questions with the analysis of aerial photographs of some suburbs of Kumasi and Accra on a temporal analytical basis. Aerial photographs together with other census data are used to estimate the present population at the time offlight. A comparison is made between population from aerial photographs and that estimated using national census data. Some assessment of the impact of population growth on the environment is made